Question
upstudy study bank question image url

8) \( \frac{3}{f+1}-\frac{1}{2}=\frac{1}{3 f+3} \)

Ask by Delgado Harris. in Argentina
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

La solución de la ecuación es \( f = \frac{13}{3} \).

Solution

Para resolver la ecuación: \[ \frac{3}{f + 1} - \frac{1}{2} = \frac{1}{3f + 3} \] **Paso 1:** Observa que \(3f + 3\) se puede factorizar como \(3(f + 1)\). Entonces, la ecuación se simplifica a: \[ \frac{3}{f + 1} - \frac{1}{2} = \frac{1}{3(f + 1)} \] **Paso 2:** Para facilitar los cálculos, hagamos un cambio de variable. Sea \(x = f + 1\). La ecuación queda: \[ \frac{3}{x} - \frac{1}{2} = \frac{1}{3x} \] **Paso 3:** Multiplicamos ambos lados de la ecuación por \(6x\) (el mínimo común múltiplo de los denominadores) para eliminar los denominadores: \[ 6x \left( \frac{3}{x} \right) - 6x \left( \frac{1}{2} \right) = 6x \left( \frac{1}{3x} \right) \] Simplificando cada término: \[ 18 - 3x = 2 \] **Paso 4:** Resolvemos para \(x\): \[ 18 - 2 = 3x \\ 16 = 3x \\ x = \frac{16}{3} \] **Paso 5:** Recordando que \(x = f + 1\), sustituimos de vuelta para encontrar \(f\): \[ f + 1 = \frac{16}{3} \\ f = \frac{16}{3} - 1 \\ f = \frac{16}{3} - \frac{3}{3} \\ f = \frac{13}{3} \] **Conclusión:** La solución de la ecuación es: \[ f = \frac{13}{3} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( \frac{3}{f+1}-\frac{1}{2}=\frac{1}{3f+3} \), first, observe that \( 3f + 3 = 3(f + 1) \). This allows us to reframe the equation: \[ \frac{3}{f+1} - \frac{1}{2} = \frac{1}{3(f + 1)} \] Now, let's find a common denominator for the left-hand side, which will be \( 2(f + 1) \): \[ \frac{3 \cdot 2}{2(f + 1)} - \frac{(f + 1)}{2(f + 1)} = \frac{6 - (f + 1)}{2(f + 1)} = \frac{5 - f}{2(f + 1)} \] So, the equation now looks like: \[ \frac{5 - f}{2(f + 1)} = \frac{1}{3(f + 1)} \] Next, eliminate the denominators by multiplying each side by \( 6(f + 1) \): \[ 6(5 - f) = 2 \] This simplifies to: \[ 30 - 6f = 2 \] Rearranging gives: \[ 28 = 6f \quad \Rightarrow \quad f = \frac{28}{6} = \frac{14}{3} \] Thus, the solution is: \[ f = \frac{14}{3} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy